2017
DOI: 10.1136/bmjgast-2016-000116
|View full text |Cite
|
Sign up to set email alerts
|

How bad is bile acid diarrhoea: an online survey of patient-reported symptoms and outcomes

Abstract: ObjectivesBile acid diarrhoea (BAD) is an underdiagnosed condition producing diarrhoea, urgency and fear of faecal incontinence. How patients experience these symptoms has not previously been studied. Bile Acid Malabsorption (BAM) Support UK was established in 2015 as a national charity with objectives including to provide details regarding how BAD affects patients, to improve earlier recognition and clinical management.Design, setting and main outcomeA questionnaire was collected anonymously by BAM Support UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 10 publications
3
72
0
5
Order By: Relevance
“…Almost half of patients diagnosed with BAM/BAD have to wait for more than 5 years to be diagnosed and many patients feel that their symptoms are repeatedly dismissed until the diagnosis is made 26. Yet, it has been estimated that a full-time general practitioner sees on average eight patients with IBS-like symptoms a week (one of whom is presenting for the first time)27 and this costs the National Health Service £22 million for these consultations28 and more than £70 million for prescribed treatments for IBS annually 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost half of patients diagnosed with BAM/BAD have to wait for more than 5 years to be diagnosed and many patients feel that their symptoms are repeatedly dismissed until the diagnosis is made 26. Yet, it has been estimated that a full-time general practitioner sees on average eight patients with IBS-like symptoms a week (one of whom is presenting for the first time)27 and this costs the National Health Service £22 million for these consultations28 and more than £70 million for prescribed treatments for IBS annually 29.…”
Section: Discussionmentioning
confidence: 99%
“…Formal testing is now the diagnostic approach recommended 8. This seems entirely reasonable as it has become clearer that empirical therapy does not always give clear-cut results,34 and this may contribute to the large group of patients with BAM/BAD who have had their diagnosis missed repeatedly, the so-called ‘revolving door’ effect where people with IBS-like symptoms have repeated referrals and investigations but do not respond to treatments offered 26…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis can be made by SeHCAT scanning in a relatively simple, non-invasive procedure, which gives a greater proportion of positive results than other, less proven tests 4. Patients value having the correct diagnosis made in a timely fashion; almost half of those in a recent survey had waited for more than 5 years and felt that their symptoms had been dismissed before they were diagnosed with PBAD 11. Treatment with bile acid sequestrants is effective in a majority, as demonstrated in 75% of these patients in our previous publication 12.…”
Section: Discussionmentioning
confidence: 99%
“…Although such expert opinion recognises the value of SeHCAT testing in clinical practice, an economic review for National Institute for Health and Care Excellence in 2012 found there was insufficient data for clear conclusions to be drawn 9. Guidelines for the investigation of chronic diarrhoea are in need of updating10 and recent patient-reported symptoms and outcomes suggest many patients suffer for over 5 years as clinician awareness of appropriate diagnostic methods is not widespread 11…”
Section: Introductionmentioning
confidence: 99%
“…Excess colonic bile acids result in secretion, increased motility, and symptoms of loose stools, frequency and urgency, which patients report adversely impact on quality of life . Raised colonic bile acids can be secondary to malabsorption, as in ileal Crohn's disease, or result from impaired regulation of synthesis and overproduction of hepatic bile acids in primary BAD .…”
mentioning
confidence: 99%